Climate Change Denial and Public Relations: Strategic communication and interest groups in climate inaction - Almiron, Núria; Xifra, Jordi (Routledge New Directions in PR & Communication Research, 2020)
This is the first book on climate change denial and lobbying that combines the ideology of denial and the role of anthropocentrism in the study of interest groups and communication strategy. Climate Change Denial and Public Relations: Strategic Communication and Interest Groups in Climate Inaction is a critical approach to climate change denial from a strategic communication perspective. The book aims to provide an in-depth analysis of how strategic communication by interest groups is contributing to climate change inaction. It does this from a multidisciplinary perspective that expands the usual approach of climate change denialism and introduces a critical reflection on the roots of the problem, including the ethics of the denialist ideology and the rhetoric and role of climate change advocacy. Topics addressed include the power of persuasive narratives and discourses constructed to support climate inaction by lobbies and think tanks, the dominant human supremacist view and the patriarchal roots of denialists and advocates of climate change alike, the knowledge coalitions of the climate think tank networks, the denial strategies related to climate change of the nuclear, oil, and agrifood lobbies, the role of public relations firms, the anthropocentric roots of public relations, taboo topics such as human overpopulation and meat-eating, and the technological myth. This unique volume is recommended reading for students and scholars of communication and public relations.